2019
DOI: 10.1111/gcb.14644
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the impacts of cover crops on nitrogen leaching, net greenhouse gas balance and crop productivity

Abstract: Cover crops play an increasingly important role in improving soil quality, reducing agricultural inputs and improving environmental sustainability. The main objectives of this critical global review and systematic analysis were to assess cover crop practices in the context of their impacts on nitrogen leaching, net greenhouse gas balances (NGHGB) and crop productivity. Only studies that investigated the impacts of cover crops and measured one or a combination of nitrogen leaching, soil organic carbon (SOC), ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
279
4
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(378 citation statements)
references
References 108 publications
(168 reference statements)
19
279
4
5
Order By: Relevance
“…These results are consistent with recent simulation studies by Tribouillois, Constantin, and Justes (2018) when applying the STICS soil-crop model to 12 cropping systems in five locations in France, and with Lugato, Bampa, Panagos, Montanarella, and Jones (2014) when conducting large-scale simulations with CENTURY in Europe. Similar results were reported from field experiments conducted under various environmental conditions (García-González, Hontoria, Gabriel, Alonso-Ayuso, & Quemada, 2018;Mazzoncini, Sapkota, Bàrberi, Antichi, & Risaliti, 2011;Quemada, Cabrera, & McCracken, 1997;Thomsen & Christensen, 2004) and summarized in two meta-analysis (Abdalla et al, 2019;Aguilera et al, 2013;Poeplau & Don, 2015). All these studies agree that the mitigation potential of soil C sequestration is finite because this pool eventually reaches a steady state.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with recent simulation studies by Tribouillois, Constantin, and Justes (2018) when applying the STICS soil-crop model to 12 cropping systems in five locations in France, and with Lugato, Bampa, Panagos, Montanarella, and Jones (2014) when conducting large-scale simulations with CENTURY in Europe. Similar results were reported from field experiments conducted under various environmental conditions (García-González, Hontoria, Gabriel, Alonso-Ayuso, & Quemada, 2018;Mazzoncini, Sapkota, Bàrberi, Antichi, & Risaliti, 2011;Quemada, Cabrera, & McCracken, 1997;Thomsen & Christensen, 2004) and summarized in two meta-analysis (Abdalla et al, 2019;Aguilera et al, 2013;Poeplau & Don, 2015). All these studies agree that the mitigation potential of soil C sequestration is finite because this pool eventually reaches a steady state.…”
Section: Discussionsupporting
confidence: 83%
“…The yield reduction observed in a minority of sampling locations might be due to the competition for water by the cover crops over the main crop (Mediterranean, Central Europe). Results from a meta‐analysis by Abdalla et al () identified a stabilization or a slight reduction of grain yield (4% on average with respect to the fallow control) as a drawback for cover cropping adoption, and suggested that management practices adapted to local conditions could mitigate this disadvantage. In our study, the yield reduction under the GHG 0 and GHG min scenarios compared to the CC leg scenario highlighted the transition toward a more N limiting environment in many of the simulated locations by 2100.…”
Section: Discussionmentioning
confidence: 99%
“…Most of what we know about the inefficiency of N fertilizer use comes from temperate North America, Europe, and Asia (Liu et al, 2010). Although there have been a number of recent meta-analyses on N losses from agroecosystems, they include very few observations from tropical agriculture (Abdalla et al, 2019;Liu et al, 2017;Shcherbak et al, 2014;Zhou & Butterbach-Bahl, 2014). For example, Shcherbak et al, 2014 included only five studies from the tropics.…”
mentioning
confidence: 99%
“…The types of CC used and the planting and termination times could also affect the grain yield. Studies have emphasized mixed results of CC use on grain yield, reporting reduced grain yields with spring‐sown CC due to high competition with primary crop for resources (Känkänen et al, 2003), no effects on grain yield (Ohlander et al, 1996), and reduced yields by monocropped CC and increased yields by legume and nonlegume CC mixtures (Abdalla et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Miguez and Bollero (2005) reported mixed effects of winter CC use on corn ( Zea mays L.) yields in the United States and Canada with a 21% increase of corn yield after a biculture mix of legume and grass species winter CC, a 37% yield increase after legume winter CC, and no yield benefit after a grass winter CC. A review by Abdalla et al (2019) reported ∼4% reduction of grain yield of the primary crop compared with the control by both legume and nonlegume CC, as well as an increase of yield up to ∼13% by cover crop mixtures.…”
mentioning
confidence: 99%